2021
DOI: 10.1021/acssuschemeng.1c01148
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Ester-Decorated Cellulose Nanocrystals as UV-Absorbing Nanoreinforcements in Polyvinyl Alcohol Films

Abstract: Grafting novel and nature-inspired phenolic esters onto cellulose nanocrystals (CNCs) provides nanofibers with excellent protection against UV radiation when incorporated into a polymer matrix. In this work, CNCs decorated with a novel UVabsorbing phenolic diester (CNC-diethyl ferulate or CNC-DEF) obtained via a click-type copper-catalyzed azide/alkyne cycloaddition reaction were incorporated into a polyvinyl alcohol (PVA) matrix to produce transparent films with excellent photostability and UV-absorbing prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…From Figures 3A-C, the nanofibers on the surface of CNF film are arranged and randomly distributed, thus forming a dense network interwoven structure under 300 um. As can be seen from Figures 3D-F, the surface of the CNF film became more smooth after being soaked in PVA solution, and the internal pores were filled with PVA solution, which became more compact (Mendoza et al, 2021). From Figures 3G,H,L, it could be seen that the surface of the film after silane modification became rough and has small protruding antennae, which was the main reason for the film superhydrophobicity.…”
Section: Sem and Roughness Testmentioning
confidence: 90%
“…From Figures 3A-C, the nanofibers on the surface of CNF film are arranged and randomly distributed, thus forming a dense network interwoven structure under 300 um. As can be seen from Figures 3D-F, the surface of the CNF film became more smooth after being soaked in PVA solution, and the internal pores were filled with PVA solution, which became more compact (Mendoza et al, 2021). From Figures 3G,H,L, it could be seen that the surface of the film after silane modification became rough and has small protruding antennae, which was the main reason for the film superhydrophobicity.…”
Section: Sem and Roughness Testmentioning
confidence: 90%
“…Such molecules turned out to provide a full coverage of the UV-A and UV-B regions of the electromagnetic spectrum, by increasing the conjugation throughout a longer backbone. It is noteworthy to mention that the free phenol can also be functionalized in order to be grafted onto materials—providing them with anti-UV properties ( Peyrot et al, 2020a ; Joram Mendoza et al, 2020 ; Mendoza et al, 2021a ; Mendoza et al, 2021b )—or even be used for polymerization to directly provide anti-UV materials ( Sasiwilaskorn et al, 2008 ). As previously mentioned, an increased steric hinderance on the β position is a key factor to improve absorption and stability against UV radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Grafting functional polymers onto nanocellulose has been investigated to produce smart materials for advanced applications . Nanocellulose, which can either be cellulose nanofibers (CNFs), cellulose nanocrystals (CNCs), or bacterial cellulose (BC), has been widely used as a building block and scaffold for polymer functionalization because of desirable properties such as great abundance and sustainability, excellent mechanical behavior, unique optical properties, and tunable surface chemistry. Due to the high density of hydroxyl groups present on its surface, nanocellulose can easily be functionalized by a variety of chemical reactions to graft polymers. Indeed, several studies on polymer-grafted nanocellulose materials demonstrated stimuli responsive and other functional properties as reported in the literature …”
Section: Introductionmentioning
confidence: 99%